Los efectos de las actividades de la concesión minera El Corazón, dentro del ecosistema de la microcuenca del río Verde Chico (Tema Central) - Endara Espinosa, María de Loreto (2025)
This study aims to analyze the activities of the El Corazón mining concession, an anthropogenic operation situated in the buffer zone of Cotacachi Cayapas National Park in Imbabura. It also explores the concept of nature as a legal subject that must be studied and protected by professionals in disaster risk management. The objective was to assess the impacts of mining activities on the Verde Chico and Los Monos water ravines, both located within the Río Verde Chico microbasin, particularly regarding the use of cyanide in daily operations. The methodology employed was descriptive, utilizing information gathered about the El Corazón mining concession from El Corazón Agroindustrial Company “Agrocorazón,” with data collected by the Environmental Corporation “Association of Owners of the Rural Areas of the North” (APT-Norte) through public information requests. This investigation also raised concerns about the availability of weather station data. Chemical analyses were conducted on the water from both ravines, along with an assessment of the ichthyofauna present. The findings revealed a lack of historical precipitation data from INAMHI. In conclusion, the El Corazón mine significantly alters the natural water systems, complicating the understanding of local biodiversity and landscape dynamics.